Factors influencing concurrent wasting, stunting, and underweight among children under five who suffered from severe acute malnutrition in low- and middle-income countries: a systematic review - Dassie, Godana Arero; Chala Fantaye, Tesfaye; Charkos, Tesfaye Getachew; Sento Erba, Midhakso; Balcha Tolosa, Fufa (Frontiers in Nutrition, 2024)
Background Wasting, stunting, and underweight in children are complex health challenges shaped by a combination of immediate, underlying, and systemic factors. Even though copious data demonstrates that the causation routes for stunting and wasting are similar, little is known about the correlations between the diseases in low- and middle-income nations. Objective The objective of this study is to evaluate the factors that concurrently affect wasting, stunting, and underweight in <5-year-olds with severe acute malnutrition (SAM). Method This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched every electronic database that was available, from the medRxiv pre-print site, PubMed, MEDLINE, EMBASE, Cochrane Library, Web of Science, PsycINFO, CINAHL, Google Scholar, and Scopus, in addition to the Science Direct search engine. We considered research conducted in low- and middle-income nations on <5-year-olds with SAM. The Newcastle Ottawa Scale was used to assess the quality of the studies. Results After screening and selecting 12 eligible studies, 1,434,207 records were included for analysis. The prevalence of factors influencing concurrent wasting, stunting, and being underweight was 26.42% in low-middle -income countries (LMI). The prevalence was higher in men, with wasting, stunting, and underweight at 14.2, 4.1, and 27.6%, respectively. Unprotected drinking water was associated with stunting [odds ratio = 0.68; 95CI (0.50, 0.92)]. Being male is another factor (aOR = 2.04, 95% CI: 1.13, 3.68). Lack of prenatal care follow-up was associated with a lower risk of wasting (OR = 2.20, 95% CI: 1.04, 4.64), while low birth weight (<2.5 kg), diarrhea, having a younger child, and being from a poor household were associated with wasting, stunting, and underweight. Other factors included body mass index (BMI) for age aOR = 2.11, 95% CI: (0.07, 0.895); maternal education: stunting [aOR = 1.52, 95% CI: (0.09, 0.89)], underweight [aOR = 1.97, 95% CI: (0.01, 0.73)], and open defecation, stunting [aOR = 1.62, 95% CI: (0.06, 0.32)], underweight [aOR = 1.92, 95% CI: (0.042, 0.257)]). Likelihood of being underweight increased with birth order (second born, aOR = 1.92, 95% CI 1.09–3.36; third born, aOR = 6.77, 95% CI 2.00–22.82). Conclusion Inadequate dietary intake, illness, food insecurity, poor maternal and child care, poor hygiene and sanitation, and healthcare inaccessibility contribute to SAM.